Appetite and its association with mortality in patients with advanced cancer – a Post-hoc Analysis from the Palliative D-study - Charlotte Goodrose-Flores; Stephanie E. Bonn; Caritha Klasson; Maria Helde Frankling; Ylva Trolle Lagerros; Linda Björkhem-Bergman (BMC Palliative Care, 2023)
Abstract Background Loss of appetite is a common nutrition symptom in patients with cancer. Understanding the trajectory of appetite could be of clinical use for prognostication in palliative cancer care. Our primary aim was to explore the association between self-assessed appetite and mortality in patients suffering from advanced cancer. Secondary aims included the relation between fatigue, albumin levels and CRP/albumin ratio and mortality. We also aimed to study potential sex-differences in the associations. Methods Post-hoc analyses were performed using data from the Palliative D-study comprising 530 patients with cancer admitted to palliative care. Appetite and fatigue were assessed with the Edmonton Symptom Assessment System (ESAS). Cox proportional hazards models were used to calculate Hazard ratios (HR) with 95% confidence intervals (CI) for exposures of appetite, fatigue, albumin and CRP/albumin ratio, and time from study inclusion to death or censoring. Analyses were also performed stratified by sex. Results The follow-up time ranged between 7 to 1420 days. Moderate and poor appetite were significantly associated with a higher mortality rate compared to reporting a good appetite; HR 1.44 (95%CI: 1.16–1.79) and HR 1.78 (95%CI: 1.39–2.29), respectively. A higher mortality rate was also seen among participants reporting severe fatigue compared to those reporting no fatigue; HR 1.84 (95%CI:1.43–2.36). Participants with low albumin levels (< 25 g/L) and those in the highest tertile of CRP/albumin ratio, had higher mortality rates, HR 5.35 (95%CI:3.75–7.63) and HR 2.66 (95%CI:212–3.35), compared to participants with high albumin levels (> 36 g/L) and those in lowest tertile of CRP/albumin ratio. These associations were more pronounced in men than in women. Conclusion Poor appetite, severe fatigue, low albumin level and a high CRP/albumin ratio were associated with increased mortality rates among patients with advanced cancer. All these variables might be clinically useful for prognostication in palliative cancer care. Trial registration Clinicaltrial.gov. Identifier: NCT03038516;31, January 2017.